Socioeconomic Precariousness in Times of Covid-19: A Human Rights Quandary under the ECHR (Polish Yearbook of International Law, 2021)
The COVID-19 pandemic, and pandemics in general, affect socioeconomically disadvantaged people more severely. This is due not only to their precarious living, health, and working conditions, but also to public actions and omissions. However, their plight remains mostly invisible to the public, governments, and legislators, which raises many questions regarding respect of their fundamental rights. In this contribution, I explore these questions in light of the European Convention on Human Rights (ECHR). On the basis of the corpus of literature in the field and the European Court of Human Rights (ECtHR) case law, I show that the Strasbourg Court has developed some protection for people in a precarious situation, especially under the prohibition of inhuman and degrading treatment and the right to private and family life. This case law is likely to be relevant to the protection of socioeconomically underprivileged people during pandemics. However, this protection is limited and imbued with pitfalls. Against this background, I show that there is an urgent need for practitioners and courts to explore an additional tool under the ECHR: the prohibition of discrimination on grounds of socioeconomic status. This tool can be used to tackle issues of misrecognition which particularly affect socioeconomically underprivileged people, who are more severely affected by public actions and omissions in the context of the current pandemic.